Engineering Site Classification for Hilla City's Nadir Highway Project, Iraq: A Novel Correlation of Shear Wave Velocity and N-SPT Value (Iraqi National Journal of Earth Science (INJES), 2026)
Assessing earthquake risks is crucial. The risks come due to the great destruction caused by earthquakes, which depend heavily on the movement of tectonic plates. One technique for determining earthquake movement characteristics in a specific area is studying the shear wave velocity (Vs). This study uses an empirical equation tailored for clayey silt soils to explore the relationship between shear wave velocity (Vs) and Standard Penetration Test (SPT) N-values. Subsurface soil investigations are performed at Nadir Highway intersection site in Hilla City. SPT-N values are obtained from four borehole wells alongside corresponding shear wave velocity measurements from Multichannel Analysis of Surface Waves (MASW). An empirical equation is developed through regression analyses of the collected data to relate the SPT-N values to Vs, facilitating the estimation of shear wave velocity based on SPT results. Vs-measured values are then employed to estimate the Vs-expected value at the site or at sites closely resembling it in terms of N-values in cases where Vs measurements are unavailable. Based on the Iraqi Seismic Code 303 and the estimated Vs value, the site is classified as class D (hard soil). This classification provides insights into the potential seismic behavior of the site and can be used to inform earthquake hazard mitigation strategies.
Keywords: Shear Wave Velocity, SPT-N values, Hilla Soil, Empirical Equation, MASW